Grand Challenges of Interdisciplinarity: The Management of Medical Risk - Žic Fuchs, Milena (Array, 2010)
The notions of interdisciplinarity and monodisciplinarity in the management of medical risk are discussed. These notions are of essential importance because management of medical risk goes well beyond medical issues. The notions of knowledge-led (research driven) interdisciplinarity and risk (crisis) induced interdisciplinarity (associated with Grand Challenges) is developed. The importance of Humanities and Social Sciences input is viewed from the perspective of the individual ↔ family ↔ social groups ↔ national context as well as the awareness and understanding of global implications of man’s activities and global risks.